2005
DOI: 10.1002/job.330
|View full text |Cite
|
Sign up to set email alerts
|

Attracting retirees to apply: desired organizational characteristics of bridge employment

Abstract: SummaryThis research examined the impact of three organizational policies on applicant attraction of 120 older workers with an interest in bridge employment (i.e., work after formal retirement). Using a mock newspaper ad to manipulate policies, scheduling flexibility, and a targeted equal employment opportunity (EEO) statement positively influenced older workers' attraction to the organization, while opportunities to transfer knowledge had little impact. A significant and positive three-way interaction suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 42 publications
(53 reference statements)
3
68
0
2
Order By: Relevance
“…However, research also shows that older workers in bridge jobs have higher access to flexible work options than older workers in career jobs (ArmstrongStassen, 2008a,b). This is striking given that the attractiveness of jobs increases when flexibility is part of the job, as the vignette study among retirees showed (Rau & Adams, 2005). Moreover, Armstrong-Stassen (2008b) showed that flexibility is important for people in bridge jobs to remain employed and not to retire.…”
Section: Employee Perceptions On Workplace Flexibility For Older Workersmentioning
confidence: 99%
See 4 more Smart Citations
“…However, research also shows that older workers in bridge jobs have higher access to flexible work options than older workers in career jobs (ArmstrongStassen, 2008a,b). This is striking given that the attractiveness of jobs increases when flexibility is part of the job, as the vignette study among retirees showed (Rau & Adams, 2005). Moreover, Armstrong-Stassen (2008b) showed that flexibility is important for people in bridge jobs to remain employed and not to retire.…”
Section: Employee Perceptions On Workplace Flexibility For Older Workersmentioning
confidence: 99%
“…Workplace flexibility has been linked to the aging workforce for some time as a way older workers can be motivated, retained, and made to maintain productivity at higher ages (Rau & Adams, 2005;Siegenthaler & Brenner, 2000). This represents a shift from the research on flexible work schedules which until then primarily focused on availability and use for women and young parents (Brewer, 2000).…”
Section: Workplace Flexibility Across the Lifespanmentioning
confidence: 99%
See 3 more Smart Citations